Genomic impact of CRISPR immunization against bacteriophages. (20th November 2013) - Barrangou, Rodolphe; Coûté-Monvoisin, Anne-Claire; Stahl, Buffy; Chavichvily, Isabelle; Damange, Florian; Romero, Dennis A.; Boyaval, Patrick; Fremaux, Christophe; Horvath, Philippe
Abstract : CRISPR (clustered regularly interspaced short palindromic repeats) together with cas (CRISPR-associated) genes form the CRISPR–Cas immune system, which provides sequence-specific adaptive immunity against foreign genetic elements in bacteria and archaea. Immunity is acquired by the integration of short stretches of invasive DNA as novel 'spacers' into CRISPR loci. Subsequently, these immune markers are transcribed and generate small non-coding interfering RNAs that specifically guide nucleases for sequence-specific cleavage of complementary sequences. Among the four CRISPR–Cas systems present in Streptococcus thermophilus, CRISPR1 and CRISPR3 have the ability to readily acquire new spacers following bacteriophage or plasmid exposure. In order to investigate the impact of building CRISPR-encoded immunity on the host chromosome, we determined the genome sequence of a BIM (bacteriophage-insensitive mutant) derived from the DGCC7710 model organism, after four consecutive rounds of bacteriophage challenge. As expected, active CRISPR loci evolved via polarized addition of several novel spacers following exposure to bacteriophages. Although analysis of the draft genome sequence revealed a variety of SNPs (single nucleotide polymorphisms) and INDELs (insertions/deletions), most of the in silico differences were not validated by Sanger re-sequencing. In addition, two SNPs and two small INDELs were identified and tracked in the intermediate variants. Overall, building CRISPR-encoded immunity does not significantly affect the genome, which allows the maintenance of important functional properties in isogenic CRISPR mutants. This is critical for the development and formulation of sustainable and robust next-generation starter cultures with increased industrial lifespans.